PD-1+ IFN-γ+ subset of CD8+ T cell in circulation predicts response to anti–PD-1 therapy in NSCLC - Chen, Wenxiu; Hua, Yiting; Shan, Conghui; Wei, Jia; Zhou, Yutong; Pan, Shiyang (Frontiers in Oncology, 2023)
Background Treatment with programmed cell death protein-1 (PD-1) antibodies has minimal response rates in patients with non-small cell lung cancer (NSCLC) and actually they are treated with chemotherapy combined with anti-PD-1 therapy clinically. Reliable markers based on circulating immune cell subsets to predict curative effect are still scarce. Methods We included 30 patients with NSCLC treated with nivolumab or atezolizumab plus platinum drugs between 2021 and 2022. Whole blood was collected at baseline (before treatment with nivolumab or atezolizumab). The percentage of circulating PD-1+ IFN-γ+ subset of CD8+ T cell was determined by flow cytometry. The proportion of PD-1+ IFN-γ+ was calculated after gating on CD8+ T cells. Neutrophil/lymphocyte ratio (NLR), relative eosinophil count (%) and LDH concentration at baseline of included patients were extracted from electronic medical records. Results The percentage of circulating PD-1+ IFN-γ+ subset of CD8+ T cell at baseline in responders were significantly higher than those in non-responders (P<0.05). Relative eosinophil count (%) and LDH concentration in responders showed no significance between non-responders and responders. NLR in responders were significantly lower than those in non-responders (P<0.05). Receiver operation characteristics (ROC) analysis found that the areas under curve (AUCs) for PD-1+ IFN-γ+ subset of CD8+ T cell and NLR were 0.7781 (95%CI 0.5937–0.9526) and 0.7315 (95%CI 0.5169–0.9461). Besides, high percentage of PD-1+ IFN-γ+ subset in CD8+ T cells was relevant to long progression-free survival (PFS) in NSCLC patients treated with chemotherapy combined with anti-PD-1 therapy. Conclusions The percentage of circulating PD-1+ IFN-γ+ subset of CD8+ T cell could be a potential marker at baseline to predict early response or progression in patients with NSCLC receiving chemotherapy combined with anti-PD-1 therapy.